Clinical guidelines and their implementation. Issue 843 (January 1996) - Forrest, D.; Hoskins, A.; Hussey, R.
Abstract : Within the UK there has been increasing interest in the development and implementation of guidelines, as the emphasis on clinical effectiveness is gathering momentum. This paper outlines some of the practical issues encountered in developing and implementing guidelines, based on experiences within Liverpool. Developing local guidelines can be a lengthy process, but that process is not a waste of time if it means there is more likely to be compliance in the end. Dissemination of guidelines alone is not enough; it needs to be combined with an appropriate implementation strategy. There is a danger of primary care being overloaded with new guidelines; there needs to be a timed strategy for their introduction. More imaginative thought needs to be put into the marketing of new ideas in order to change practice. We need to encourage the ethos amongst healthcare professionals of expecting to have to constantly update knowledge and practice.